Erratum to Significance of the lymph nodes in the 7th station in rational dissection for metastasis of distal gastric cancer with different T categories - Team, Editorial (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Erratum to: Chin J Cancer Res 2014;26:423-30